(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Currently, many companies are willing to help Micro and Small Enterprises (MSMEs) in the form of Corporate Social Responsibility (CSR). Corporate Social Responsibility (CSR) is a concept or action taken by the company as the company’s responsibility for the surrounding environment where the company is located, namely carrying out an activity that can improve the welfare of the surrounding community and protect the environment, in the form of providing funds for funeral public facilities, donations to build community facility that is social and useful for the community at large, especially the community around the company. One of the CSR activities is in the form of social improvement by strengthening the economy of the community around the company’s working area, in the form of strengthening MSMEs (Micro, Small and Medium Enterprises) in terms of providing capital assistance. In this research, the writer designed the Corporate Architectural Planning of the program. From this program the authors hope that the Corporate Architectural Planning can be a solution. The company architecture planning can be developed in the future for development. This investigation is the author’s project in 2015.